Difference Analysis and Optimization Short-Term Income Manegemen Changes Before And After Capital Market Supervisory Agency Over Mandatory Disclosures Annual Report - Dedi Putra SE,.M.S.Ak; Pebrina Swissia; Taufik Taufik; Agus Panjahitan (Prosiding International conference on Information Technology and Business (ICITB), 2019)
This study aims to provide empirical evidence that companies are optimizing the short term in order to achieve a certain profit target (to avoid reporting losses and a decrease in income) have mandatory information disclosure level is low. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange period 2016-2018. The sample selection using purposive sampling method, observation data obtained 40 Hypothesis testing using different test Paired Sample T test, with a confidence level of 95%. These results indicate that the Amendment Regulation of Capital Market Supervisory Board on mandatory disclosure of the annual report does not affect the Company's Profit Optimization and Short-Term Management, seen from the test results showed no difference.Keywords: Corporate Profits, Optimizing the Management of Short-Term